A Comprehensive Review of Milk Components: Recent Developments on Extraction and Analysis Methods - Maria Assunta Acquavia; Antonio Villone; Roberto Rubino; Giuliana Bianco (Molecules)
In recent years, there has been a growing interest in identifying both the macro- and micro-constituents of milk, as their functional and health benefits have been recognized. This review provides a comprehensive overview of all milk constituents, including fats, proteins, oligosaccharides and polysaccharides, vitamins, minerals and polyphenols, along with their extraction protocols and the analytical methods employed for their separation and detection over the last ten years. The principles, strengths and limitations of these methods are discussed, highlighting their importance in advancing milk research. Traditional methods such as spectrophotometry, and advanced technologies, like mass spectrometry and omics approaches, are described to collectively enable a comprehensive understanding of milk’s nutritional and functional components. Election criteria for the analytical platforms suitable for target analytes are provided.